Application of Artificial Intelligence In Medical Decision Making - Dewi, Sarini Vita (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2017)
The information system of artificial intelligence (Artifical Intellegance) is very much needed in various fields of science. Softcomputing technology is a field of study is interdisciplinary research in computational science and artificial intelligence. For example, where some of the techniques in softcomputing including expert systems (expert systems), neural networks (Neural Networks), fuzzy logic (fuzzy logic), and genetic algorithms (genetic algorithms) began to be applied in applications that help humans in running kan tasks and achieve certain objectives to be achieved.One sub-field that uses artificial intelligence system to address and analyze an existing problems is the field of medicine. The development of artificial intelligence applications in the medical field is very helpful to some users involved in medicine such as doctors and patients.Keywords: artificial, system